Pengaruh Karakteristik Pekerjaan Kerja, Etos Kerja dan Kualitas Kehidupan Kerja terhadap Kinerja Pegawai : Studi pada Pegawai Kantor Kecamatan Lowokwaru Kota Malang - Maria Mince Mea; Adya Hermawati; Soedjono Soedjono (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The purpose of this study was to study how job characteristics, work ethic, and quality of life affect employee performance at the Lowokwaru District Office, Malang City. In addition, the purpose of this research analysis was to determine how the independent and dependent variables used in this study interact with each other. This study used the entire population as a sample. where the author used 31 employees at the Lowokwaru District Office as a research sample. The tool used in this study was the Likert scale, which consisted of five response options, each valued 1-5. This study used research instruments, multiple linear regression analysis, and hypothesis testing with the help of Windows SPSS 4.0. The results of this study indicate that job characteristics, work ethic, and quality of life have a partial and positive effect on employee performance. Based on these findings, it can be concluded that all independent variables in this study have an effect on the dependent variable.